Design method for steel restrainer bars on railway bridges subjected to spatially varying earthquakes. (15th March 2018) - Liu, Cong; Gao, Ri
Highlights: The theory for the mechanical properties of the restrainer is proposed. Hysteretic test and numerical analyses of the restrainer are conducted. An elastic-plastic design procedure for the steel restrainer bar is developed. Time history analyses are conducted comparing with the design method. The rail effect is analyzed to evaluate the effectiveness of the restrainer. Abstract: The unseating and pounding damage at expansion joints during earthquakes emphasizes the need to restrain the relative opening and closing displacements between adjacent bridge spans. Traditional cable restrainers perform well in preventing unseating damage but may increase the pounding damage between adjacent decks sometimes. Considering the limitation of the cable restrainer, a steel restrainer bar installed between a pier and a deck is proposed to restrain both the relative opening and closing displacement to prevent unseating and pounding damage to railway bridges. In this paper, theoretical formulas for the mechanical properties of the restrainer bar, experiments and numerical analyses are conducted. A design procedure for the steel restrainer bar, which considers spatially varying earthquakes and the hysteretic behaviour of the restrainer, is developed. The procedure accounts for the dynamic out-of-phase motion characteristics between adjacent bridge spans, and the pounding is assumed to be completely avoided by the restrainer bar. A series of case studies with different pier heights and different earthquake characteristics are conducted to evaluate the effectiveness of the design method; the time history analysis results are consistent with the case study results. The restraint effect of the rails is also considered in this paper. The results of the numerical analyses reveal that both the pier height and the rails significantly influence the effectiveness of the steel restrainer bar. As the pier height increases, the effectiveness of the restrainer in reducing the relative displacement also increases, whereas the effectiveness in mitigating shear decreases with a pier height greater than 15 m. The rails reduce the effectiveness of the steel restrainer bar when subjected to spatially varying ground motions.